Selecting high-income generating activities for micro-entrepreneurs: the case study of Amanah Ikhtiar Malaysia - Md Saad, Norma (Centre for Promoting Ideas, 2011)
Poverty eradication has been one of the most important concerns in developing countries. Many of the governments of these countries have initiated some forms of poverty alleviation programs to reduce poverty level in their respective countries. Studies have shown that microfinance is proven to be an effective tool to fight poverty in many developing countries. This study looks at various income generating activities taken up by micro-entrepreneurs who obtained micro-credit from Amanah Ikhtiar Malaysia (AIM), the biggest microfinance institution in Malaysia, and identifies which activities result in high income. A survey was conducted to obtain primary data on economic activities assumed by AIM members and also income obtained from these activities. The results of the survey show that economic activities in the trading sector are found to be very lucrative and result in higher average income compared to activities in the production and service sectors. Among activities which result in high monthly incomes are rubber trading, sales of cooking gas, hawking in night markets, sales of cosmetics and body wear, paint products, jewellery, used cars, electronics, health products, and food.